The Fragility of Democracy: Political Conflict in South Asia - Thapa, Santa Bahadur (Prajnik Bimarsha प्राज्ञिक विमर्श, 2024)
The complex interplay between political conflict and democratic fragility in South Asia is the focus of this research paper. The study examines South Asia to understand how conflict catalyzes and hinders democratic progress. The research delves deep into the root causes of conflict, including socio-economic disparities, ethnic and religious tensions, and institutional weaknesses. It analyzes how conflict can trigger democratic reforms through popular mobilization and erode governance and institutions. The study highlights the fragility of democratic systems in the face of deep-rooted conflicts and the challenges of balancing competing interests. It underscores the need for South Asian nations to address underlying grievances to strengthen democratic institutions and foster inclusive dialogue to navigate conflict constructively and secure a stable democratic future. The research employs a qualitative approach, relying on a comprehensive literature review and case study analysis to draw insights into the multifaceted relationship between political conflict and democratic development in the selected region.